Prevalence and Severity of Dental Attrition in a Sample of Kurdish Patients in Erbil City - Rebaz Samir Ismail; Lana Burhan Ali; Reem Zeyad Naja; Iman Haider Mustafa; Anas Jamal Rashid; Trifa Sardar Adnan; Rupak Othman Saad; Yousif Hawar Mawlood (Eurasian Journal of Science and Engineering)
Tooth attrition is a non-caries lesion worn off the tooth's incisal and occlusal surface and belongs to the wasting disease group. This study aims to determine the prevalence and severity of tooth attrition concerning gender, age groups, and tooth-grinding habits in a sample of Kurdish patients in Erbil. The research encompasses 176 cases from both genders (88 males, 88 females) clinically examined for attrition. The result demonstrates that 93% of all participants have at least one sign of attrition. In other words, 97% of patients within the age group of 40 years and older suffered from the prevalence of dental attrition. Meanwhile, the number decreases to only 90% of patients for the age group of less than 40 years.